2008
DOI: 10.1148/radiol.2482072169
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a “Triple Rule-Out” Coronary CT Angiography Protocol: Use of 64-Section CT in Low-to-Moderate Risk Emergency Department Patients Suspected of Having Acute Coronary Syndrome

Abstract: Triple rule-out coronary CT angiography evaluation of low-to-moderate risk ACS patients presenting to the ED provided a noncoronary diagnosis that explained the presenting complaint in 11% of patients, suggested the presence of significant moderate-to-severe coronary disease in 11% (22 of 197) of patients, and precluded additional diagnostic cardiac testing in the majority of patients with no adverse outcomes at 30-day follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
83
3
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(94 citation statements)
references
References 32 publications
7
83
3
1
Order By: Relevance
“…We and others have reported that MDCT could accurately and safely identify occluded culprit lesions in patients early after acute myocardial infarction (AMI), which may provide important information to aid in risk stratification [29,30] . In patients with acute coronary syndrome sowing ambiguous ST segment changes on electrocardiogram, MDCT adds diagnostic accuracy and helps to exclude pulmonary embolism, aortic dissection, and other thoracic disease [31] . For patients with complex coronary artery disease who require bypass surgery, the 3D-image reconstruction from MDCT also provides additional details to operators [32] .…”
Section: To the Editormentioning
confidence: 99%
“…We and others have reported that MDCT could accurately and safely identify occluded culprit lesions in patients early after acute myocardial infarction (AMI), which may provide important information to aid in risk stratification [29,30] . In patients with acute coronary syndrome sowing ambiguous ST segment changes on electrocardiogram, MDCT adds diagnostic accuracy and helps to exclude pulmonary embolism, aortic dissection, and other thoracic disease [31] . For patients with complex coronary artery disease who require bypass surgery, the 3D-image reconstruction from MDCT also provides additional details to operators [32] .…”
Section: To the Editormentioning
confidence: 99%
“…Yirmi yedi hastada ise hastanın başvuru şikayetini açıklamayacak ancak klinik açıdan önemi bulunan ek tanılara ulaşılmış. Bir ay boyunca takip edilen hastaların hiçbirisin-de önemli bir patoloji gözlenmemiştir (22).…”
Section: Triple Rule-out Bilgisayarlı Tomografiunclassified
“…More recently, with the introduction of 64-slice CT technology, it has been suggested that ''triple rule-out'' testing could become reality [15]. This would include assessment of pulmonary embolism, aortic dissection and coronary artery disease as the three main diagnostic emergencies for most physicians faced with patients with chest pain.…”
Section: Ct Pulmonary Angiographymentioning
confidence: 99%